Facilitation of Quercus ilex in Mediterranean shrubland is explained by both direct and indirect interactions mediated by herbs - Cuesta, Bárbara; Villar-Salvador, Pedro; Puértolas, Jaime; Rey Benayas, José M.; Michalet, Richard (Journal of Ecology, 2010)
1. Competitive and facilitative interactions shape plant communities. Whereas a number of studies have addressed competition and direct facilitation among plants in dry ecosystems, indirect facilitation has received little attention. 2. We investigated the relative importance of direct and indirect facilitation by the nurse plant Retama sphaerocarpa on late-successional Quercus ilex seedlings mediated by herb suppression in a Mediterranean shrubland in 2006 and 2007. We also studied whether facilitation outcome depended on the size of the facilitated seedlings. 3. A field experiment was carried out to test the effect of (i) position of Q. ilex seedling with respect to shrub canopy (under shrubs or in gaps), (ii) herb competition (presence or absence), and (iii) seedling size. 2006 was an average rainfall year while 2007 had a much more humid spring and a dryer summer than 2006. 4. In both years, nurse shrubs reduced seedling mortality whereas herbs increased it. In the average rainfall year, seedling mortality under shrubs was unaffected by herbs whereas in gaps it was significantly higher in presence of herbs. This showed that the nurse shrub indirectly facilitated the seedlings by reducing the competitive capacity of herbs. Conversely, facilitation was predominately direct during the humid spring and dry summer year since herbs hindered seedling survival similarly under the nurse shrub and in gaps. The nurse shrub directly facilitated the seedlings by reducing seedling photoinhibition and water stress. 5. Improvement of environmental conditions by Retama benefited smaller seedlings but not larger seedlings since the nurse shrub reduced mortality of smaller seedlings relative to that in gaps, but this effect was not observed for larger seedlings. This indicates that individuals within a seedling population may not have the same response to facilitation. 6. Synthesis. Both indirect and direct facilitation are important mechanisms for Q. ilex regeneration in Retama shrubland and their importance seems to vary with climatic conditions. Indirect facilitation by release of herb competition under nurse shrubs is important in years of dry springs when competition between nurse shrubs and herbs is high, whereas direct facilitation mediated by microclimate amelioration increases with summer aridity.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: chlorophyll fluorescence; herb competition; Quercus ilex; retama sphaerocarpa; seedling size; water potential